Conjugates of doxorubicin with graft HPMA copolymers for passive tumor targeting - Etrych, Tomás; Chytil, Petr; Mrkvan, Tomás; Sírová, Milada; Ríhová, Blanka; Ulbrich, Karel (Journal of controlled release, 2008)
Synthesis, physicochemical behavior, tumor accumulation and preliminary anticancer activity of a new biodegradable graft copolymer-doxorubicin (DOX) conjugates designed for passive tumor targeting were investigated. In the graft high-molecular-weight conjugates the multivalent N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer was grafted with a similar but semitelechelic HPMA copolymer; both types of polymer chains were bearing doxorubicin attached by hydrazone bonds enabling intracellular pH-controlled drug release. The polymer grafts were attached to the main chain through spacers, degradable enzymatically or reductively, facilitating, after the drug release, intracellular degradation of the graft polymer carrier to short fragments excretable from the organism by glomerular filtration. The graft polymer-DOX conjugate exhibited prolonged blood circulation and enhanced tumor accumulation in tumor-bearing mice indicating the important role of the EPR effect in the anticancer activity. The graft polymer-DOX conjugates showed a significantly higher antitumor activity in vivo than DOX.HCl or the linear polymer conjugate when tested in mice bearing 38C13 B-cell or EL4 T-cell lymphoma, with a significant number of long-term-surviving (LTS) mice with EL4 T-cell lymphoma treated with a single dose 15 mg DOX equiv./kg on day 10.
Keywords: lymfom; Hydrolysis; farmaceutická chemie; Delayed-Action Preparations; hydrolýza; Drug Carriers; molekulová hmotnost; injekce intravenózní; doxorubicin; myši inbrední C3H; Doxorubicin; Molecular Weight; Mice, Inbred C3H; Lymphoma; zvířata; myši; myši inbrední C57BL; Mice; buněčné linie; Acrylamides; akrylamidy; xenogenní modely - testy protinádorové aktivity; biologický transport; Cell Line; Male; Mice, Inbred C57BL; Hydrogen-Ion Concentration; nosiče léků; léky s prodlouženým účinkem; Chemistry, Pharmaceutical; Xenograft Model Antitumor Assays; Animals; Injections, Intravenous; mužské pohlaví; koncentrace vodíkových iontů; Antibiotics, Antineoplastic; Biological Transport; protinádorová antibiotika